Friction Torque in Miniature Ball Bearings - Denis Cojocaru; Gelu Ianuș; Vlad Cârlescu; Bogdan Chiriac; Dumitru Olaru (Lubricants)
The problem of estimation the friction torque in operating miniature ball bearings lubricated with oil or grease is a complex one. Generally, in an angular contact ball bearing (ACBB), various types of losses can appear including losses caused by kinematics in ball-race contacts (rolling, sliding and pivoting), losses between the cage and the balls and between the cage and the guiding race and losses generated by lubricant, especially at high speeds. In the miniature ACBB, the applied loads have generally low values, and some losses can be ignored. In these circumstances, the most important contribution to the increase in the losses in miniature ACBB is the presence of the lubricant. In normal rolling bearings, the lubricant has an important contribution to decrease the losses and increase the reliability in miniature ball bearing; the lubricant (oil or grease) leads to the increase in the losses compared to the dry or limit lubrication conditions. The catalogues of various rolling bearing companies have not provided more details referring to the friction losses in miniature ball bearings. In order to evaluate the total friction torque in the rolling bearings, some empirical complex relations are presented via the SKF methodology, which can be applied only to moderate and high loads applied to the rolling bearings. Other empirical relations are presented by the Schaeffler catalogue. Based on previous experiments, the authors determined the friction torque in a 7000C ACBB with the spin-down method. The experimental results were correlated with the results obtained via the theoretical model developed by Houpert for IVR lubrication conditions. The theoretical results evidenced that the hydrodynamic rolling resistance generated by the lubricant is the most important component of the friction torque for 7000C ACBB. The experimental and theoretical results were compared to the results obtained according to the SKF and Schaeffler relations. The experimental results and the results obtained with the Houpert model generally had higher values compared to the results obtained with the SKF and Schaeffler relations.